RELATIONSHIP BETWEEN INDIVIDUAL CHARACTERISTICS WITH MILD PHYSICAL COMPLAINTS POST VACCINATION TYPE MRNA-1273 IN MEDICAL PERSONNEL AT KALIDERES DISTRICT HEALTH CENTER IN 2023 - Andri Yustika; Dwi Nurmawaty; Intan Silviana Mustikawati; Ade Heryana (Sean Institute, 2023)
The mRNA-1273 vaccine has an efficacy of up to 95% and is one of the vaccines with the highest effectiveness compared to other types of vaccines. Apart from this effectiveness, the mRNA-1273 vaccine was reported to have side effects in the form of physical complaints. Based on data from the Puskesmas Kalideres, all medical personnel, or 100%, have been vaccinated with mRNA-1273. This study aims to determine the relationship between individual characteristics and mild physical complaints after mRNA-1273 vaccination in medical personnel at the Puskesmas Kalideres in 2023. This type of quantitative study used a cross-sectional design with a sample size of 117 medical personnel. This study used a total sampling technique. Data collection used primary data by way of interviews using a questionnaire. Data analysis used the Chi-Square test. The study results showed a relationship between age and mild physical complaints after mRNA-1273 vaccination (p-value 0.020; POR=5.967) in medical personnel at the Puskesmas Kalideres. Whereas for gender (p-value 1.000), controlled comorbid (p-value 0.272), and shift work (p-value 0.277), there was no association with mild physical complaints after mRNA-1273 vaccination in medical personnel at the Puskesmas Kalideres. It was recommended that the Puskesmas optimize education for Puskesmas employees and the public about the importance of booster vaccinations, both the mRNA-1273 type and other types available in health services, and explain the benefits, side effects, and handling if there are complaints.